PERCEPTUAL ASPECTS OF MUSIC LISTENING: A THEORETICAL REVIEW - Janisauska, Jana; Bernhofs, Valdis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Human beings exist within a perpetual sound environment, where ambient noises, work environment, conversations, music in supermarkets, cafes and other public establishments, as well as other sources of sound create a complex soundscape. To be able to navigate this environment, to receive timely warning signals and to participate in the communication process with the people around us, constant listening is required. Listening is our way to experience, sense, understand and coherently react to this world. Although the term “listening” by which we define this activity affects almost the entire scope of our daily lives, one of the aspects that has been of interest to a wide spectrum of specialists, including philosophers, scientists, theoreticians and teachers is the listening to music. During the last decade, the interest in the research of several components of this activity has increased also in the field of music psychology, especially in the context of neuropsychology. However, until now, no in-depth analysis of the interaction of perceptual aspects of music listening has been conducted.The purpose of this article is to provide a theoretical overview on the latest findings in the analysis of the perceptual factors in music listening, defining their mutual interaction. The findings of this article substantiate the statement that music listening can be viewed as a continuous and individualized interaction of perceptual processes that on various levels of cognition are fostered by the individual’s musical experience. The entirety of findings invites deeper analysis of the complex nature of this dual concept.